Direct coagulation casting of yttria-stabilized zirconia using magnesium citrate and glycerol diacetate. Issue 4 (May 2015) - Xu, Jie; Gan, Ke; Yang, Minghao; Qu, Yanan; Wu, Jiamin; Yang, Jinlong
Abstract: Direct coagulation casting via controlled release of high valance counter ions (DCC-HVCI) has been reported in recent years. In this paper, concentrated yttria-stabilized zirconia (YSZ) suspensions were coagulated using DCC-HVCI method with magnesium citrate as coagulating agent assisted by pH shift in the presence of glycerol diacetate. The effect of ammonium polyacrylate (PAA-NH4 ) on the dispersibility of YSZ powder was investigated. The influence of concentrations of glycerol diacetate and magnesium citrate on pH and viscosities of YSZ suspensions was studied. The results indicate that concentrated YSZ suspensions can be coagulated by adding 2 vol% glycerol diacetate and magnesium citrate above 0.5 wt% at room temperature for 2–5 h. The compressive strength of coagulated wet samples is above 2.0 MPa. YSZ ceramics sintered at 1450 °C show homogeneous microstructures with relative densities of 98.9–99.2%. Flexural strength of YSZ ceramics is 869±84 MPa.